Effects of Storage Conditions on the Astaxanthin, Moisture, and Aerobic Microorganisms of Spiced Sergestid Shrimp - Pham, An Binh; Tran, Long Bach; Cao, Thuy Xuan; Tran, Nhi Thi Yen; Vu, Ngoc Duc (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2024)
Each food product has distinct characteristics. Selecting appropriate storage conditions for each product is essential to minimize quality degradation and extend its shelf life. This study focused on understanding how different packaging materials and storage temperatures influence the quality, longevity of spiced Sergestid shrimp, and on determining the optimal conditions to inhibit microbial activity, prevent moisture absorption, while still preserving maximum astaxanthin content. Polyethylene bags with an aluminum film (Al/PE), PET bottles (polyethylene terephthalate), paper bags with a polyethylene film (Paper/PE), and glass bottles were used for packaging. Storage was carried out at four different temperatures: 5; 15; 25; 35°C. The moisture content, astaxanthin content, and total aerobic microorganisms were also determined at least once every 3 to 7 days and continuously monitored for 77 days. The findings indicated that PET bottles effectively prevent moisture absorption and protect astaxanthin from degradation over time. However, transparent packaging, such as glass bottles that allow direct exposure of the product to light, negatively affects the stability of astaxanthin. The optimal temperature range for storing this product was identified as being between 5 and 15°C, which helped stabilize moisture content (5.55-6.34%) and inhibit the growth of aerobic microorganisms (2.42-2.58 LogCFU/g). These findings provide crucial insights for the seafood industry, particularly in choosing the right packaging materials and storage conditions to enhance the shelf life and maintain the quality of spiced Sergestid shrimp products. This study contributes to the existing knowledge and aids stakeholders in making informed decisions regarding product packaging and storage strategies.